FAIRsharing – A Curated Resource On Data And Metadata Standards, With A Spotlight On Africa - Lister, Allyson (My University, 2023)
FAIRsharing is a curated, informative, and educational resource on data and metadata standards, interrelated to databases and data policies, across all disciplines. This presentation is about the documentation FAIRsharing holds and the services it provides for African research standards, databases, and more. Learn more about FAIRsharing at https://fairsharing.org.
Allyson Lister is the FAIRsharing Content & Community Lead at the University of Oxford. With a background in data standardisation, ontologies, semantic data and integration, she is responsible for FAIRsharing content, as well as for collaborations with users and outreach across all research domains. Allyson is also an EOSC Future / RDA Domain Ambassador (for standards, databases and policies), and is a co-chair of two RDA working groups. Watch the recording of this presentation at https://africarxiv.pubpub.org/pub/rnyoeatk/ This webinar session is part of the AfricArXiv Open Science Webinar Series on the Discoverability of African Research, co-organized by UbuntuNet Alliance: https://ubuntunet.net/ and Access 2 Perspectives: https://access2perspectives.org/ as part of the ORCID Global Participation Fund: https://info.orcid.org/global-participation-program/. View all sessions of this webinar series at https://africarxiv.pubpub.org/webinars Learn more about ORCID: https://orcid.org/
Keywords: FAIRsharing; SOCIAL SCIENCES::Statistics, computer and systems science::Informatics, computer and systems science::Databases; Metadata Standards